Feasibility Study of the Destination of Lake Tanjung Kurung and Kampung Inggris Tempirai, PALI Regency - Hasan, Hanif; Pratiyudha, Dilla; Mertajayano, I Made Oka; Damayati, Sri Wulan; Marini, Nadia Chairunnisa Andra Sitha; Nandana, Pandita; Gusma, Esxi Martia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research explores the potential for developing Danau Tanjung Kurung and Kampung Inggris Tempirai as promising tourist spots in PALI Regency, South Sumatra. Adopting a qualitative approach and descriptive methods, it examines the economic, social, cultural, and environmental factors associated with these locations. Data were gathered through in-depth interviews, field observations, and documentation with community members, tourism stakeholders, and local government officials. The findings highlight the natural allure of Danau Tanjung Kurung and the distinctive educational tourism experience offered by Kampung Inggris Tempirai. Nevertheless, obstacles such as insufficient infrastructure, minimal community involvement, and a lack of sustainable tourism awareness remain. The study concludes that with effective planning, stakeholder cooperation, and the adoption of sustainable practices, these destinations could bolster local economies, protect cultural heritage, and position themselves as sustainable tourism icons. Recommendations encompass infrastructure enhancements, greater community engagement, and the promotion of integrated tourism packages to draw both domestic and international tourists.